Evidence of hybrid origin for Tachyphonus nattereri Pelzeln, 1870 (Aves: Thraupidae) - Lopes, Leonardo Esteves; Piacentini, Vitor De Q. (Zootaxa, 2017)
Tachyphonus nattereri is one of the three “mystery birds” collected almost 200 years ago by J. Natterer in Brazil whose validity has been disputed in many publications over the last century. Known only from the male holotype and perhaps a female specimen without type status, it is currently treated as either a valid species, a subspecies or a doubtful taxon (an extreme of variation or an aberrant-colored individual). We reviewed the taxonomy of T. nattereri based on fieldwork near the type locality and a careful examination of the holotype and related museum specimens. Our extensive fieldwork revealed that no natural population found in the type locality matches the phenotype of T. nattereri. We found that the holotype is intermediate in plumage, morphometry and body shape between Tachyphonus cristatus and T. luctuosus, two sympatric species locally scarce and at their distributional edge around the type locality. We, therefore, suggest that T. nattereri is a hybrid. On the other hand, the purported female falls within the variation found in Tachyphonus c. madeirae, of which it probably represents an extreme phenotype.